Breast Arterial Calcification on a Screening Mammogram: A Potential Cardiovascular Risk Stratification Tool in Women - Fathala, Ahmed; Abunayyan, Deema; Zeitouni, Leena (Reviews in cardiovascular medicine, 2025)
Breast arterial calcification (BAC) is a common benign finding on a screening mammogram. Additionally, BAC is a type of medial calcification known as Mönckeberg medial calcific sclerosis, which differs from the intimal calcification seen in patients with coronary artery disease (CAD). Recently, BAC has appeared as a new cardiovascular risk stratification method. Studies have indicated a potential link between BAC and cardiovascular risk factors, particularly coronary artery calcification (CAC), as observed in coronary computed tomography. However, the association between BAC and myocardial ischemia and angiographic-proven CAD remains controversial. The usefulness of BAC during mammography as a potential screening tool for CAD has been the subject of uncertainty and debate for many years. This article reviews the current literature on BAC and its association with CAC, myocardial ischemia, and angiographic-proven CAD on both invasive and coronary computed tomography. Cardiovascular outcomes, current limitations, and future investigation and recommendations are also explored and discussed.